Full blood count parameters for the detection of asthma inflammatory phenotypes. Issue 9 (September 2014) - Zhang, X.‐Y.; Simpson, J. L.; Powell, H.; Yang, I. A.; Upham, J. W.; Reynolds, P. N.; Hodge, S.; James, A. L.; Jenkins, C.; Peters, M. J.; Lin, J.‐T.; Gibson, P. G.
Summary Background In asthma, the airway inflammatory phenotype influences clinical characteristics and treatment response. Although induced sputum is the gold standard test for phenotyping asthma, a more accessible method is needed for clinical practice. Objective To investigate whether white blood cell counts and/or their derived ratios can predict sputum eosinophils or neutrophils in uncontrolled asthma. Methods This cross‐sectional study evaluated 164 treated but uncontrolled asthmatic patients with sputum induction and blood collection. Receiver‐operating characteristic (ROC) curves were used to assess the relationship between blood and sputum parameters. Results There was a significant positive relationship between blood eosinophil parameters and the percentage of sputum eosinophil count. A weak but significant correlation was found between sputum neutrophil percentage and blood neutrophil percentage (r = 0.219, P = 0.005). ROC curve analysis identified that blood eosinophil percentage count was the best predictor for eosinophilic asthma, with an area under the curve (AUC) of 0.907 (P < 0.001). The optimum cut‐point for blood eosinophil percentage was 2.7%, and this yielded a sensitivity of 92.2% and a specificity of 75.8%. The absolute blood eosinophil count was also highly predictive with an AUC of 0.898 (P < 0.0001) at a blood eosinophil cut‐off of 0.26 × 109/L. The blood eosinophil/lymphocyte ratio (ELR) and eosinophil/neutrophil ratio (ENR) were increased in eosinophilic asthma, and the neutrophil/lymphocyte ratio (NLR) was increased in neutrophilic asthma. Neutrophilic asthma could also be detected by blood neutrophil percentages and NLR, but with less accuracy. Conclusions and Clinical Relevance Blood eosinophil counts and derived ratios (ELR and ENR) can accurately predict eosinophilic asthma in patients with persistent uncontrolled asthma despite treatment. Blood neutrophil parameters are poor surrogates for the proportion of sputum neutrophils. Blood counts may be a useful aid in the monitoring of uncontrolled asthma.